Report of the Working Group on Life Insurance Administration Vol I - Planning Commission (Planning Commission, 1968)
Under an Ordinance promulgated on the 19th January 1956 all life insurance business was nationalised by Government. The Life Insurance Corporation of India was established on the 1st September,1956 under the Life Insurance Corporation Act,1956. In his broadcast to the nation at the time of nationalisation, the Finance Minister, Shri C.D. Deshmukh, stated that the nationalisation of life insurance would be another milestone on the road the country had chosen in order to reach its goal of a Socialistic Pattern of society.
Administrative Reforms Commission
Administrative Reforms Commission